The Problems of the COVID-19 Pandemic in Higher Education - Salakhova, Valentina B.; Shukshina, Liudmila V.; Belyakova, Natalia V.; Kidinov, Alexey V.; Morozova, Natalia S.; Osipova, Natalia V. (Frontiers in Education, 2022)
At present, many studies have been undertaken around the world to find out how education reacts to the challenges of a completely new situation, when distance learning has practically become the only form of acquiring and mastering knowledge. The initiative of the consortium of participants in the World Education Leadership Symposium and the international project World School Leadership Study (WSLS) can serve as an example of an international project. In the framework of this project the data were collected and analyzed all over the world about the difficulties faced by all participants in education in connection with the pandemic and the total transition to distance learning. The desire of the entire world scientific community to cope with the global risks and challenges posed by the COVID-19 pandemic has led to the fact that today a large area of research has been accumulated on the problem of distance learning and the prospects for its development, the search for the most effective ways to solve educational problems during the pandemic. The paper presents the results of a socio-psychological study of the problem of accessibility and safety of educational resources and applications, tools of distance educational technologies for students of Moscow universities during the period of distance learning. The study included conducting in-depth interviews - an unstructured personal interview with students according to a previously prepared script (guide) with audio recording. The developed script (guide) of the interview, which provided the possibility of subsequent use of quantitative and qualitative analysis of the processing of the data obtained, was used as a toolkit. A total number of 160 students from various Moscow universities participated in the interview. The interviews were conducted from February 1, 2021 to June 1, 2021, both face-to-face and remotely. The organizational platform of the online research was the Zoom service. The analysis of the existing research results on the indicated problems, carried out by the authors of the paper, made it possible to identify several trends in the distance education development during the pandemic.